2003
DOI: 10.1002/jnr.10568
|View full text |Cite
|
Sign up to set email alerts
|

Activation of protein kinase C inhibits retrograde transport of neurotrophins in mice

Abstract: Retrograde axonal transport of neurotrophins from nerve terminal to cell body requires a number of key processes, including internalization of the receptor-neurotrophin complex into vesicles and formation of multivesicular bodies and their transport along the axon. Previous studies have shown that each of these processes can be regulated by kinases. In this study, we looked at the role of protein kinase C (PKC) in retrograde transport by injecting labeled neurotrophins together with relevant pharmacological ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Some of the earliest studies on phorbol esters noted actin filament loss and general network disorganization in epithelial (Schliwa et al ., 1984) and smooth muscle cells (Dugina et al ., 1987), effects later identified as being mediated by PKC (Hai et al ., 2002). Similar changes were observed with PKC activation in trigeminal ganglion cell (Ozsarac et al ., 2003) and DRG growth cones (Bonsall and Rehder, 1999) and in hippocampal dendritic spines (Calabrese and Halpain, 2005). In agreement with previous studies, we observed significant decreases in P-domain actin density with PKC activation (Figure 1, Supplemental Figures S2 and S4B, and Supplemental Movies S1 and S2).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Some of the earliest studies on phorbol esters noted actin filament loss and general network disorganization in epithelial (Schliwa et al ., 1984) and smooth muscle cells (Dugina et al ., 1987), effects later identified as being mediated by PKC (Hai et al ., 2002). Similar changes were observed with PKC activation in trigeminal ganglion cell (Ozsarac et al ., 2003) and DRG growth cones (Bonsall and Rehder, 1999) and in hippocampal dendritic spines (Calabrese and Halpain, 2005). In agreement with previous studies, we observed significant decreases in P-domain actin density with PKC activation (Figure 1, Supplemental Figures S2 and S4B, and Supplemental Movies S1 and S2).…”
Section: Discussionsupporting
confidence: 85%
“…In agreement with the repulsive trend, PKC activation has been associated with growth cone collapse in cervical ganglion explants (Ozsarac et al ., 2003), retraction responses in dorsal root ganglia (DRG; Bonsall and Rehder, 1999) and hippocampal neurons (Mattson et al ., 1988), and decreased neurite sprouting in neuroblastoma cells (Cressman and Shea, 1995). PKC activation also induced axon loss at the neuromuscular junction of neonatal rats (Lanuza et al ., 2002).…”
Section: Introductionsupporting
confidence: 67%
“…The overall result is that there is a large variation in the intensity of the label making accurate counting difficult. While both TrkA and p75 NTR are involved in the transport of NGF, the transport of NT3 has previously been shown to be dependent on the p75 NTR (35,36). These results taken together suggest that in many of the neurons transporting anti-DBH the predominant receptor for neurotrophin transport is the p75 NTR .…”
Section: Discussionmentioning
confidence: 70%
“…These data are consistent with the notion that somal and dendritic p75NTR can be pharmacologically induced to sort in a similar fashion as axonal p75NTR, but the resolution and differentiation is much less distinct than in the axonal in vivo system, because neurotrophins internalize in dendrites (or severed axons) at varying distances from the cell body, thereby obscuring differences in the kinetics of accumulation. We did not attempt to increase PKC activity in our ION model system in vivo, because it is known that pharmacological activation of PKC inhibits retrograde axonal transport of neurotrophins (Ozsarac et al, 2003). …”
Section: Resultsmentioning
confidence: 99%